Paradoks Perlindungan Perkawinan: Analisis Socio-Legal Terhadap Fenomena Digital Starter Wife dan Efektivitas Perjanjian Kawin di Indonesia - Safiatus Zahro; Nadya Artika Maulani; Ikwal Pangsa Chaniago; Miftahus Sholehudin (Al-Istinbath : Jurnal Ilmu Hukum dan Hukum Keluarga Islam, 2026)
The starter wife phenomenon demonstrates the existence of relationship inequality in modern marriages that is not only individual, but also structural due to the influence of patriarchal culture and the dynamics of the digital space. This study aims to analyze the starter wife phenomenon from a socio-legal perspective and examine the effectiveness of prenuptial agreements as an instrument of legal protection in the Indonesian marriage legal system. The method used is normative legal research with a legislative, conceptual, and socio-legal approach combined with a netnographic analysis of digital narratives on the social media platform TikTok. The research data consists of primary legal materials in the form of the Marriage Law and Constitutional Court Decision Number 69/PUU-XIII/2015, as well as secondary legal materials from scientific literature and non-legal data in the form of digital content representing the starter wife phenomenon. The results of the study indicate a gap between legal norms that guarantee the principle of equality between husband and wife and social realities that still perpetuate unequal gender relations, particularly in the recognition of women's non-material contributions in the household. In addition, prenuptial agreements as a preventive legal instrument have experienced an expansion of meaning, but their effectiveness remains limited due to low public legal literacy and the strong cultural stigma against agreements in marriage. This study recommends strengthening the socialization of marriage agreements through the Office of Religious Affairs, notaries, and digital legal literacy as an effort to reconstruct legal protection for marriage that is more responsive to gender justice. Abstrak Fenomena starter wife menunjukkan adanya ketimpangan relasi dalam perkawinan modern yang tidak hanya bersifat individual, tetapi juga struktural akibat pengaruh budaya patriarki dan dinamika ruang digital. Penelitian ini bertujuan untuk menganalisis fenomena starter wife dalam perspektif socio-legal serta mengkaji efektivitas perjanjian kawin sebagai instrumen perlindungan hukum dalam sistem hukum perkawinan Indonesia. Metode yang digunakan adalah penelitian hukum normatif dengan pendekatan perundang-undangan, konseptual, dan socio-legal yang dipadukan dengan analisis netnografi terhadap narasi digital pada platform media sosial TikTok. Data penelitian terdiri atas bahan hukum primer berupa Undang-Undang Perkawinan dan Putusan Mahkamah Konstitusi Nomor 69/PUU-XIII/2015, serta bahan hukum sekunder dari literatur ilmiah dan data non-hukum berupa konten digital yang merepresentasikan fenomena starter wife. Hasil penelitian menunjukkan adanya kesenjangan antara norma hukum yang menjamin prinsip kesetaraan suami-istri dengan realitas sosial yang masih melanggengkan ketimpangan relasi gender, khususnya dalam pengakuan kontribusi non-material perempuan dalam rumah tangga. Selain itu, perjanjian kawin sebagai instrumen hukum preventif telah mengalami perluasan makna, namun efektivitasnya masih terbatas akibat rendahnya literasi hukum masyarakat dan kuatnya stigma budaya terhadap perjanjian dalam perkawinan. Penelitian ini merekomendasikan penguatan sosialisasi perjanjian kawin melalui Kantor Urusan Agama, notaris, serta literasi hukum digital sebagai upaya rekonstruksi perlindungan hukum perkawinan yang lebih responsif terhadap keadilan gender.